A proposal for the etiopathogenesis of acquired cold urticaria: Role of substance p, angiotensin-converting enzyme and mast cell chymase - Çaytemel, Ceyda; Türko?lu, Zafer; A?ırgöl, Şenay; Ustao?lu, Eda; Topaloğlu Demir, Filiz; Uzuner, Esen (Wolters Kluwer Medknow Publications, 2022)
Background: The etiopathogenesis and cold stimulation mechanism are not fully understood in cold urticaria (CU). Substance P (SP) is released from skin neurons as a result of cold stimulation. It causes mast cell degranulation and therefore causes mast cell chymase (MCC) release. Angiotensin-converting enzyme (ACE) plays a role in removing SP from the environment. ACE also catalyses the conversion of angiotensin I (AT1) to angiotensin II (AT2), like MCC. This study aims to investigate the role of SP, ACE and MCC in the pathogenesis of CU. Methods: Patients with acquired CU were included in the study. Two punch biopsies were taken from the urticaria plaque resulting from the stimulation and the intact skin without lesions. The samples were evaluated histopathologically. All samples were stained immunohistochemically with SP, ACE and MCC antibodies. Results: The number of patients included in the study was 21. In the plaque lesion, the presence of dermal neutrophil and eosinophil, neutrophil in the vascular lumen were found to be statistically significantly higher than intact tissue (p = 0.046, P = 0.014, P = 0.014). Strong positive staining was detected in the full thickness of the epidermis, vascular endothelial cells, eccrine and sebaceous glands with ACE. MCC was statistically significantly higher in lesional skin than lesion-free skin samples (p < 0.001). Conclusions: Mast cell maintains its central role in CU pathogenesis. SP, which causes neurogenic inflammation, may not be detected due to its rapid destruction in the tissue. Strong staining of ACE, which takes part in the local renin-Angiotensin-Aldosterone (RAS) system in the skin, should be documented quantitatively.
Keywords: Angiotensin-Converting Enzyme; Chymase; Cold Urticaria; Inducible Urticaria; Mast Cell; Substance P